ANALISIS DISIPLIN, MOTIVASI, DAN LOYALITAS TERHADAP KINERJA KARYAWAN DI DIVISI OUT BOUND PT JNE EXPRESS CABANG UTAMA MEDAN - Rambe, Azli Firmansyah; Waruwu, Ahmad Aswan (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
This study aims to analyze the influence of work discipline, work motivation, and loyalty on employee performance in the Out Bound Division of PT JNE Express Medan Main Branch. Using a quantitative method and associative approach, the study involved 40 permanent employees as samples. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that both partially and simultaneously, work discipline, work motivation, and loyalty have a positive and significant impact on employee performance. Work discipline is the most dominant factor influencing employee performance, followed by motivation and loyalty. Therefore, enhancing work discipline and motivation, as well as employee loyalty, can be an effective strategy to improve performance within the company. Keywords: Work Discipline, Work Motivation, Loyalty, Employee Performance, PT JNE Express.